Reduced electron recombination of dye-sensitized solar cells based on TiO2 spheres consisting of ultrathin nanosheets with [001] facet exposed - Wang, Hongxia; Liu, Meinan; Yan, Cheng; Bell, John (Beilstein Journal of Nanotechnology, 2012)
An anatase TiO2 material with hierarchically structured spheres consisting of ultrathin nanosheets with 100% of the [001] facet exposed was employed to fabricate dye-sensitized solar cells (DSCs). Investigation of the electron transport and back reaction of the DSCs by electrochemical impedance spectroscopy showed that the spheres had a threefold lower electron recombination rate compared to the conventional TiO2 nanoparticles. In contrast, the effective electron diffusion coefficient, Dn, was not sensitive to the variation of the TiO2 morphology. The TiO2 spheres showed the same Dn as that of the nanoparticles. The influence of TiCl4 post-treatment on the conduction band of the TiO2 spheres and on the kinetics of electron transport and back reactions was also investigated. It was found that the TiCl4 post-treatment caused a downward shift of the TiO2 conduction band edge by 30 meV. Meanwhile, a fourfold increase of the effective electron lifetime of the DSC was also observed after TiCl4 treatment. The synergistic effect of the variation of the TiO2 conduction band and the electron recombination determined the open-circuit voltage of the DSC.
Keywords: dye-sensitized solar cells; electrochemical impedance spectroscopy; electron recombination; TiO2 [001] facet; ultrathin nanosheets